Processing Mobile Transactions In MDRTDBS (Mobile Distributed Real-Time Database Systems) (Journal of Namibian Studies : History Politics Culture, 2021)
The proliferation of mobile devices has led to an increase in mobile transactions, necessitating efficient processing mechanisms in Mobile Distributed Real-Time Database Systems (MDRTDBS). This paper explores the unique challenges posed by mobile transactions, such as variability in network connectivity and resource constraints, and proposes strategies to enhance their processing efficiency.Our study examines existing approaches to transaction management in MDRTDBS, highlighting their strengths and limitations. We introduce a novel framework that leverages adaptive concurrency control and dynamic resource management to optimize transaction processing. Performance evaluations demonstrate the superiority of our framework in terms of transaction throughput and response time under varying network conditions.The findings of this research contribute to the advancement of MDRTDBS, providing a foundation for future innovations in mobile transaction processing. This study aims to bridge the gap between theoretical models and practical applications, ensuring seamless mobile transactions in real-time distributed environments.